2015
DOI: 10.1371/journal.pone.0133968
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment Frequency and Dosing Interval of Ranibizumab and Aflibercept for Neovascular Age-Related Macular Degeneration in Routine Clinical Practice in the USA

Abstract: PurposeTo compare treatment patterns of intravitreal ranibizumab and aflibercept for the management of neovascular age-related macular degeneration (nAMD) in a real-world setting over the first 12 months of treatment.MethodsA proprietary clinical database was used to identify treatment-naïve patients with nAMD in the USA with claims for ranibizumab or aflibercept between November 1, 2011 and November 30, 2013 and with follow-up of at least 12 months. Patients were considered treatment-naïve if they had no anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 21 publications
2
47
1
Order By: Relevance
“…) and dosing interval or number of visits are also similar (Ferreira et al. ). The design of the studies leaves space for further exploration.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…) and dosing interval or number of visits are also similar (Ferreira et al. ). The design of the studies leaves space for further exploration.…”
Section: Introductionmentioning
confidence: 75%
“…The few studies comparing ranibizumab and aflibercept include ones based on administrative claims data (Ferreira et al. ; Schmid et al. ), a Bayesian network meta‐analysis of a systematic literature review (Szabo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Our study, which was carried out in routine daily practice, confirms optimal vision gains and anatomic disease control previously reported in two large clinical trials involving more than 2,400 patients with nvAMD [25] as well as in the 96-week extension of these trials [26]. Also, a number of observational studies have shown the beneficial effect of aflibercept therapy for nvAMD in both resistant to other VEGF inhibitors (bevacizumab and ranibizumab) [27,28,29,31,32] and as first line in clinical practice [33,34]. …”
Section: Discussionmentioning
confidence: 99%
“…261 However, a recent study comparing aflibercept and ranibizumab treatment patterns for AMD showed that the number of injections patients receive is comparable in the first year of treatment with aflibercept or ranibizumab; this may render the previously reported aflibercept-associated benefits of a decreased treatment and compliance burden and injection-related risks inapplicable. 262 In another study, aflibercept was found to have greater efficacy for improving visual acuity in patients with diabetic macular edema in comparison to bevacizumab and ranibizumab, while also allowing for a greater interval of time between injections. 263 The FDA has approved aflibercept under the trade name Eylea for the treatment of wet AMD and diabetic retinopathy in patients with diabetic macular edema.…”
Section: Modulation Of Lymphangiogenesismentioning
confidence: 98%